A Novel Data Classification and Scheduling Scheme in the Virtualization of Wireless Sensor Networks. (25th July 2013) - Islam, Md. Motaharul; Huh, Eui-Nam
Abstract : Most of the nodes in a wireless sensor network (WSN) remain idle for the maximum period of their lifetime resulting in underutilization of their resources. There are many ongoing research studies to utilize the resources of sensor nodes in an efficient way. Virtualization of sensor network (VSN) is one of the novel approaches to utilize the physical infrastructure of a WSN. VSN can be simply defined as the virtual version of a WSN over the physical sensor infrastructure. By allowing sensor nodes to coexist on a shared physical substrate, VSN may provide flexibility, cost effectiveness, and manageability. This paper proposes a QoS-aware data classification and scheduling framework for VSN in the health care sector. We develop a tiny virtual machine called VSNware for health care applications, which facilitates QoS-aware forwarding of data packets, maintaining the reliability, delay guarantee, and speed. The simulation results also show that the proposed scheme outperforms the conventional WSN approaches.